From Classics To Individualization: Surgical Tactics In Age-Related Ptosis Of The Eyelids And Face - Boymurodov Shukhrat Abduzhalilovich; Yusupov Shokhrukh Shukhratovich; Iminov Komilzhon Odilzhonovich; Abdurakhmonov Kakhramon Abdukakhkhor ugli; Tukhtaboyev Boburzhon Bakhodirzhon ugli (Genius Journals, 2025)
This article presents the experience of surgical correction of age-related changes in the face and periorbital region, based on the analysis of 1,450 operations performed over a 10-year period at the multidisciplinary clinic of the Tashkent Medical Academy (TMA). Modern techniques of blepharoplasty and facelifting are considered, with an emphasis on the transition from standard methods to individualized tactics that take into account the anatomical and functional characteristics of each patient. Special attention is paid to working with deep soft tissue structures, rational repositioning, and fixation of anatomical units, which made it possible to increase the safety of interventions and the predictability of aesthetic results. It has been shown that an individualized approach and the justified combination of various surgical techniques help minimize complications, improve aesthetic and functional outcomes, and meet the current requirements of aesthetic medicine
Keywords: blepharoplasty; age-related ptosis; facelift